ASTER 20th Anniversary - Abrams, Michael J. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The Advanced Thermal Emission and Reflection Radiometer (ASTER) is a research facility instrument on NASA's Terra spacecraft. We celebrated the 20th anniversary of ASTER's launch in December 1999. ASTER has been providing high spatial resolution multispectral data in the VNIR, SWIR, and TIR regions, and along-track stereo data. Starting April 2016, ASTER data have been distributed to the public at no cost. Another important and the most popular data set is the ASTER Global DEM, which covers almost the entire land surface at a 30 m grid size. ASTER data have been widely used in a variety of application areas such as land surface mapping and change detection, volcano and other natural hazard monitoring, mineral exploration, and urban heat island monitoring. This Special Issue consists of 12 papers (2 reviews, 9 articles, and 1 technical note) and covers topics including development of new techniques to process ASTER data, calibration activities to ensure long-term consistency of ASTER data, validation of the ASTER data products, and scientific achievements using ASTER data.